Socialization of Waste Management on Household Waste Sorting in Undrusbinangun Village, Sukabumi Regency - Zulfahmi Yasir Yunan; Balyana Muhtarum; Diah Ramadiani; Faza Rizfa Azkia; Firhaniah Nufadhilah; Muhamad Ridwan; Shofi Aulia; Fauziyah Anindita (PT FORMOSA CENDEKIA GLOBAL, 2022)
The waste problem in Sukabumi Regency, especially in Undrusbinangun Village, Kadudampit District, Sukabumi Regency has not been completely resolved, as there is still a lack of knowledge about how to process household waste. The handling of waste problems in Undrusbinangun Village must start from the source, namely the household by involving the active participation of the community. Awareness and concern for handling waste by the village community is still lacking. This is marked by the habit of burning waste that is still inherent in the community in managing waste. The purpose of this activity is for the community to have self-awareness not to throw garbage indiscriminately, let alone throw it into rivers and into ravines, and for the community to be able to sort household waste according to the types of waste, how dangerous it is to dispose of waste carelessly, how to implement it. waste management with the 3R concept and so on. Descriptive qualitative research method with an inductive approach. This research technique was carried out by means of field surveys, focus group discussions (FGD) involving participants, open interviews, and literature studies